Investigating the Effect of Job Demands on Job Engagement - Mohammad Rahim Rahnama; Omid Ali Kharazmi; Fateme Beygi Nasrabadi (مطالعات مدیریت بهبود و تحول, 2015)
Job demands (consisting of challenge demands and hindrance demands) are significant antecedents of job engagement. The aim of this study is to evaluate the impact of challenge demands and hindrance demands on job engagement and determining the most effective indicators of challenge demands and hindrance demands. Data were collected from 80 employees of Vice Chancellor for Planning and Development of Municipality of Mashhad by questionnaire. Descriptive data analysis and structural equation modeling were used. The results showed that challenge demands affect on job engagement positively and hindrance demands affect on job engagement negatively. Other results show that time urgency affect on challenge demands more than other factors and organizational politics effect on hindrance demands more than other factors. In addition the results also show that in the scope of study job engagement and challenge demands level is more than moderate and hindrance demands level is moderate